2003
DOI: 10.1071/sr02081
|View full text |Cite
|
Sign up to set email alerts
|

Field study of pesticide leaching in an allophanic soil in New Zealand. 2: Comparison of simulations from four leaching models

Abstract: Seven pesticides were applied to an allophanic silt loam along with a bromide tracer and their concentrations in soil and water monitored over a 2-year period. Inverse modelling was carried out using GLEAMS, LEACHM, and HYDRUS-2D to derive field-based mobility and degradation parameters. Hexazinone and procymidone were more mobile and more persistent than most literature values would suggest, whereas picloram and triclopyr were much less mobile but more persistent. The greater mobility for hexazinone, a weak b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Amorphous allophanic clays have a high isoelectric point of pH 6.0 (Cooper and Morgan, 1979), and Waihou soils have a topsoil field pH that is typically less than that (Table 2), so the allophane has a net positive surface charge (McLeod et al, 2001) and thus has an affinity for anions. Sorption of Br in allophanic soils has already been reported (Close et al, 2003). Although Br was also adsorbed in Atiamuri pumice soil ( K d = 0.01 L kg −1 for topsoil and 0.03 L kg −1 for subsoil) and Hamilton clay loam ( K d = 0.00 for topsoil and 0.03 L kg −1 for subsoil), the degree of adsorption was not high enough to cause a shift in the concentration peak.…”
Section: Resultsmentioning
confidence: 85%
“…Amorphous allophanic clays have a high isoelectric point of pH 6.0 (Cooper and Morgan, 1979), and Waihou soils have a topsoil field pH that is typically less than that (Table 2), so the allophane has a net positive surface charge (McLeod et al, 2001) and thus has an affinity for anions. Sorption of Br in allophanic soils has already been reported (Close et al, 2003). Although Br was also adsorbed in Atiamuri pumice soil ( K d = 0.01 L kg −1 for topsoil and 0.03 L kg −1 for subsoil) and Hamilton clay loam ( K d = 0.00 for topsoil and 0.03 L kg −1 for subsoil), the degree of adsorption was not high enough to cause a shift in the concentration peak.…”
Section: Resultsmentioning
confidence: 85%
“…Since 1993, some field trials have been conducted in New Zealand to assess pesticide behaviour in key New Zealand soils under different climatic conditions. The pesticide mobility and persistence characteristics derived from these field sites vary according to the type of soil and the climatic conditions and are often significantly different from those reported in the literature 3–6. For example, Close et al 6 found that procymidone was far less sorbed in pumice soils ( K oc = 352 ml g −1 ) than would be expected from the literature value ( K oc = 1500 ml g −1 ).…”
Section: Introductionmentioning
confidence: 67%
“…Tritiated water ( 3 H 2 O) was used as a conservative tracer to indicate groundwater flow and the physical characteristics of the aquifer. Bromide was tested for conservative behaviour in the pumice sand aquifer since a significant sorption of this had been found in shallow soils at the same site (unpublished results and Reference 16). Rhodamine WT was used as a visual aid for detecting peak concentrations and the main flow line.…”
Section: Methodsmentioning
confidence: 99%